2015
DOI: 10.1007/8904_2015_423
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick Type C-2 Disease: Identification by Analysis of Plasma Cholestane-3β,5α,6β-Triol and Further Insight into the Clinical Phenotype

Abstract: Introduction: Niemann-Pick type C disease is a rare disorder caused by impaired intracellular lipid transport due to mutations in either the NPC1 or the NPC2 gene. Ninety-five % of NPC patients show mutations in the NPC1 gene. A much smaller number of patients suffer from NPC2 disease and present respiratory failure as one of the most frequent symptoms. Several plasma oxysterols are highly elevated in NPC1 and can be used as a biomarker in the diagnosis of NPC1.Methods: Plasma cholestane-3b,5a,6b-triol was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…A potential source of bias in this retrospective study, however, is that non-neonatal NPC1 patients were used as surrogates for assay validation because of the lack of authentic dried blood spots from NPC1 neonates (the youngest patient in the study was 4 months old and neurologically asymptomatic). Nonetheless, in light of case reports demonstrating dramatic elevation of the bile acid precursor cholestane-3β,5α,6β-triol in NPC1 and NPC2 neonates (31), it seems probable that the bile acids will be elevated in NPC patients during the neonatal period. Moreover, bile acid B concentrations were independent of age and severity of disease, suggesting that the screening test will be universally applicable to all NPC1 subjects, including neonates.…”
Section: Discussionmentioning
confidence: 99%
“…A potential source of bias in this retrospective study, however, is that non-neonatal NPC1 patients were used as surrogates for assay validation because of the lack of authentic dried blood spots from NPC1 neonates (the youngest patient in the study was 4 months old and neurologically asymptomatic). Nonetheless, in light of case reports demonstrating dramatic elevation of the bile acid precursor cholestane-3β,5α,6β-triol in NPC1 and NPC2 neonates (31), it seems probable that the bile acids will be elevated in NPC patients during the neonatal period. Moreover, bile acid B concentrations were independent of age and severity of disease, suggesting that the screening test will be universally applicable to all NPC1 subjects, including neonates.…”
Section: Discussionmentioning
confidence: 99%
“…The chitotriosidase activity was measured as previously described ( Reunert et al, 2015 , Hollak et al, 1994 ).…”
Section: Methodsmentioning
confidence: 99%
“…The oxidation products of cholesterol, called oxysterols, can be measured by GC–MS or LC–MS/MS in human plasma. It has been shown that 7-ketocholesterol (7-KC) and cholestane-3β,5α,6β-triol (c-triol), are elevated in the plasma of NP-C1 and NP-C2 patients ( Porter et al, 2010 , Boenzi et al, 2014 , Reunert et al, 2015 , Jiang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early lung disease in patients with Niemann-Pick disease type C2 may be associated with PAP. 58,80 In Griese et al 58 and Reunert et al, 80 empirical treatment with WLL in those patients was only transiently effective, reducing the need for oxygen and improving imaging. The amount of protein recovered was low, which also differentiated this form of PAP from the others (Fig 3 A and B).…”
Section: Mars Mutationsmentioning
confidence: 99%
“…E, Over-time variation of protein washed out is shown. The detailed descriptions of the PAP cases used here can be found for GM-CSF-Ra -1 in Griese et al,27 for GM-CSF-Ra -2 in Hildebrandt et al 14 (subject I), for NPC2 in Reunert et al80 (subject 1), for SP-C (I73T) in Brasch et al, 8 for SP-C (C121F) in van Hoorn et al,81 and for MDS DiGeorge2 in Griese et al49 (subject 7). Ethics approval is documented in the individual studies.…”
mentioning
confidence: 99%